Investigating genes encoding pln A and pln EF bacteriocins from lactobacilli isolated from traditional dairy products. - Dabir, Sina; Bonab, Zahra Hojjati; Soltanzadeh, Hossein (International Journal of Travel Medicine & Global Health, 2025)
Introduction: Lactobacilli are long, gram-positive bacilli. The food industry widely uses lactic acid bacteria (LAB) as natural preservatives due to their ability to produce antibacterial compounds such as bacteriocins. The purpose of this study is to investigate the genes and beneficial lactobacilli from traditional yogurt and cheese of northwestern Iran in 1401. Methods: For this purpose, 29 samples of traditional dairy products, including 18 samples of cheese and 11 samples of yogurt, were collected under sterile conditions and inoculated in MRS culture medium. Additional tests were performed to identify them and molecular PCR tests were performed to detect the presence of plnA, plnEF genes in the isolates. In this research, after isolating Lactobacillus from traditional yogurt and cheese samples, the presence of plnEF bacteriocin gene was confirmed in 7 Lactobacillus isolates and the absence of plnA gene in the isolates. Results: In previous studies that succeeded in isolating Lactobacillus strains from traditional dairy products, plantaricin EF is present in all pln positions. In this research, after Lactobacillus was isolated from samples, two genes encoding bacteriocin plnA and plnEF were investigated in Lactobacillus isolates, plnEF was present in all of them and plnA was not present in any of the isolates. Bacteriocins induce beneficial health properties in probiotic products. Conclusion: we succeeded in isolating and identifying lactobacilli from the traditional yogurt and cheese of the northwestern region of the country by the method of culture and biochemical identification and isolation based on PCR.